PELATIHAN PSIKOEDUKASI BYSTANDER INTERVENTION PROGRAM: MAMPUKAH MENJADI SALAH SATU UPAYA PENCEGAHAN KEKERASAN SEKSUAL YANG EFEKTIF DI LINGKUNGAN KAMPUS? - Mudin, Muhammad Ilham; Sari, Diana Tanjung; Fadillah, Annisa; Harahap, Shalom Duta Putra; Nurendah, Gemala (Universitas Gunadarma, 2024)
Sexual violence in Indonesia is one of the biggest problems that must be overcome immediately, especially in the campus environment. One of the attempts that can be conducted is to afford bystander intervention programs in psychoeducation training form. This study determines the effectiveness of the bystander intervention program called Do Something to reduce rape myth acceptance and increase empathy, assertiveness, and bystander intervention behavior. This research used a within-subjects design with four times measurements (before and after the first intervention, after the second intervention, and after two weeks of follow-up). The research participants were 14 students of Indonesia University of Education aged 18-25 years who had never participated in psychoeducation activities on sexual violence. The measuring instruments used in this study consisted of 4 measuring instruments, namely Illinois Rape Myth Acceptance Scale – Subtle Version (IRMA-S), Interpersonal Reactivity Index (IRI), Functional Assertiveness Scale (FAS), dan Bystander Intervention Behavior Scale (BIBS). The results of the study showed that the Do Something 'bystander intervention program' was successful in having short-term effectiveness in women in reducing rape myth acceptance, increasing assertiveness, and bystander intervention behavior. It is expected that this program would be beneficial training in preventing sexual violence in the campus environment.